2014
DOI: 10.1016/j.jcf.2014.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectases at early chest computed tomography in children with cystic fibrosis are associated with increased risk of subsequent pulmonary exacerbations and chronic pseudomonas infection

Abstract: In CF children free from chronic PsA, both CT scores and FEV1 values demonstrate significant correlation with disease severity in the subsequent 6 years but CT score has higher predictive value in the identification of patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
(49 reference statements)
1
18
0
2
Order By: Relevance
“…The role of bronchiectasis as a robust predictive marker has been shown in several longitudinal observations [150,[155][156][157][158][159]. The extent of bronchiectasis at baseline can predict the number of respiratory tract exacerbations (RTE) [155][156][157][158], and the change of the subscore in a two year follow up is strongly associated with numbers of RTEs where FEV1 did not provide value [156]. This has been similarly described for a decade long observational study [158].…”
Section: Clinical Valuementioning
confidence: 62%
See 1 more Smart Citation
“…The role of bronchiectasis as a robust predictive marker has been shown in several longitudinal observations [150,[155][156][157][158][159]. The extent of bronchiectasis at baseline can predict the number of respiratory tract exacerbations (RTE) [155][156][157][158], and the change of the subscore in a two year follow up is strongly associated with numbers of RTEs where FEV1 did not provide value [156]. This has been similarly described for a decade long observational study [158].…”
Section: Clinical Valuementioning
confidence: 62%
“…In this context scoring of bronchiectasis particularly in the lung periphery is important [137], whereas air trapping, mosaic perfusion, and mucus plugging seem to be more sensitive markers than CT or MRI which detect effects of interventions [153,154]. The role of bronchiectasis as a robust predictive marker has been shown in several longitudinal observations [150,[155][156][157][158][159]. The extent of bronchiectasis at baseline can predict the number of respiratory tract exacerbations (RTE) [155][156][157][158], and the change of the subscore in a two year follow up is strongly associated with numbers of RTEs where FEV1 did not provide value [156].…”
Section: Clinical Valuementioning
confidence: 99%
“…Automated reading of CT chest in school‐age CF patients correlated with expert readings when assessing bronchiectasis via visual airway counts and air trapping by lung attenuation density indices . Children 4–11 years of age who had higher CT chest scores for bronchiectasis had a higher rate of pulmonary exacerbations over the next 6 years; those who also had a low FEV 1 and FEV1% predicted of 25–75% were more susceptible to chronic PA . Presence or absence of structural changes on a CT chest scan 3 years later was predicted by LCI .…”
Section: Diagnosismentioning
confidence: 99%
“…Clinical trials increasingly use CT to monitor response to antibiotics and gene therapy in the treatment of CF [17,18] . Although quantification of changes in disease severity by CT closely correlates with the frequency of infective exa cerbations and disease progression [19,20] , one must remain cognisant of the radiation dose incurred from this method of assessment [21] . Recent studies have shown that the dose from dose optimised CT scans is equivalent to onethird of one year's background radiation [22] .…”
Section: Ct Use and Cumulative Effective Dosementioning
confidence: 99%